2004
DOI: 10.1093/ndt/gfh541
|View full text |Cite
|
Sign up to set email alerts
|

Duration of end-stage renal disease and kidney transplant outcome

Abstract: This study of USRDS records suggests that a short (<6 months) dialysis course has no detrimental effect on graft and patient survival, and should not be deferred if medically indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(124 citation statements)
references
References 15 publications
6
110
0
4
Order By: Relevance
“…Furthermore, prolonged dialysis before transplant appears to have a detrimental effect on post-transplant outcomes (17)(18)(19). Goldfarb-Rumyantzev et al (17) found a 25% to 46% increase in graft failure for those transplanted after 6 mo to 5 yr of end stage kidney disease and 32% greater risk of death overall for those transplanted after 3 yr of end stage kidney disease. Therefore, it is important to identify factors associated with prolonged time in the process toward kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, prolonged dialysis before transplant appears to have a detrimental effect on post-transplant outcomes (17)(18)(19). Goldfarb-Rumyantzev et al (17) found a 25% to 46% increase in graft failure for those transplanted after 6 mo to 5 yr of end stage kidney disease and 32% greater risk of death overall for those transplanted after 3 yr of end stage kidney disease. Therefore, it is important to identify factors associated with prolonged time in the process toward kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Na análise multivariada, a sobrevida dos pacientes foi significantemente distinta entre os três grupos. Goldfarb-Rumyantzev et al 25 concluíram que um tempo prolongado de diálise está associado a resultados insatisfatórios, tanto para o enxerto como para a sobrevida do paciente após TR.…”
Section: Sobrevida E Fatores Associados à Mortalidade Em Receptores Dunclassified
“…5,9 Because transplants are associated with better long-term survival than dialysis, 10 preemptive transplant may increase survival by reducing dialysis time. Indeed, preemptive transplant has been associated with better patient and allograft survival rates and decreased acute rejection rates, compared with nonpreemptive transplant.…”
Section: Discussionmentioning
confidence: 99%